Generalized swelling and convulsions in a 6-year-old boy: Atypical presentation of ectopic Cushing syndrome (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2026)
Ectopic Cushing syndrome is an exceptionally rare condition in the pediatric population, particularly when arising from a thymic carcinoid tumor. We report the case of a six-year-old boy who presented with generalized swelling, moon face, acne, weight gain, hyperpigmentation, hypertension, and seizures. Biochemical evaluation demonstrated elevated cortisol and ACTH levels, unsuppressed by dexamethasone, indicating ACTH-dependent Cushing syndrome. Imaging revealed an anterior mediastinal mass, which was surgically excised and confirmed histologically as a thymic carcinoid tumor. Postoperatively, the patient required corticosteroid replacement, with gradual improvement of clinical features on follow-up. This case underscores the importance of considering ectopic ACTH secretion in children with rapidly progressive hypercortisolism and highlights the need for timely diagnosis and multidisciplinary management for favorable outcomes.[J Assoc Clin Endocrinol Diabetol Bangladesh, January 2026; 5(1): 60-65]